2009
DOI: 10.1016/j.pain.2009.01.011
|View full text |Cite
|
Sign up to set email alerts
|

A possible neural basis for stress-induced hyperalgesia

Abstract: Intense stress and fear have long been known to give rise to a suppression of pain termed "stressinduced analgesia," mediated by brainstem pain-modulating circuitry, including pain-inhibiting neurons of the rostral ventromedial medulla. However, stress does not invariably suppress pain, and indeed, may exacerbate it. Although there is a growing support for the idea of "stress-induced hyperalgesia," the neurobiological basis for this effect remains almost entirely unknown. Using simultaneous single-cell recordi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
111
1
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 137 publications
(128 citation statements)
references
References 74 publications
(104 reference statements)
14
111
1
2
Order By: Relevance
“…The holding temperature obviates any concern that apparent effects on reflex latency could be attributed to changes in skin temperature. Previous work has shown that response latencies and neuronal response properties are stable for a period of several hours with this testing protocol (Edelmayer et al 2009;Heinricher et al 2004Heinricher et al , 2010Kincaid et al 2006;Martenson et al 2009). …”
Section: E T H O D Smentioning
confidence: 89%
“…The holding temperature obviates any concern that apparent effects on reflex latency could be attributed to changes in skin temperature. Previous work has shown that response latencies and neuronal response properties are stable for a period of several hours with this testing protocol (Edelmayer et al 2009;Heinricher et al 2004Heinricher et al , 2010Kincaid et al 2006;Martenson et al 2009). …”
Section: E T H O D Smentioning
confidence: 89%
“…50 While the exact mechanisms responsible for emotional modulation of pain are not fully understood, heightened anxiety appears to increase sensitivity to pain (hyperalgesia), [51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][66][67][68] while moderate fear inhibits pain (hypoalgesia). 51,[69][70][71][72][73][74][75][76][77] This suggests that anticipation of an unpredictable, threatening intervention could result in enhanced pain, while hypoalgesia results from exposure to a predictable, threatening event (fear). 51 As we did not assess the participants' psychological state, we are unsure whether this changed over the course of the experiment.…”
Section: Discussionmentioning
confidence: 99%
“…An important point is that the animals did not present analgesia immediately after 20 minutes of restraint, showing that these animals were not able to respond with stress-induced analgesia (SIA) or 20 min of restraint is not enough to promote SIA. Unlike acute stress, which has been related to a reduction in pain sensitivity, probably mediated by brainstem pain modulation 42 , chronic stress exposure has been associated with decreased pain threshold. Indeed, chronic stress is associated with increased sensitivity to pain, producing hyperalgesia 19,22,43,44 , and allodynia 19,43 .…”
Section: Discussionmentioning
confidence: 99%
“…Under these conditions, we can also suggest that data found in our study may be related to an effect of stress on the opioid system. Another possibility is that the activation of stress-related circuitry in the hypothalamus activates pain-facilitating neurons in the rostral ventromedial medulla to produce hyperalgesia, suggesting possible changes in brain activity 42 . It has also been postulated that the opioid system, which is an important modulator of the descending pathway of pain, could be implicated in the pain suppression mechanism 48 .…”
Section: Discussionmentioning
confidence: 99%